Validasi Tes Keterampilan Bermain Bolavoli untuk Mahasiswa Pendidikan Jasmani - Setyo Budiwanto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
The aim of this study was to construct a test measuring students’ ability in playing volley ball. The sample were taken from male students of Physical Education Department at State University of Malang using cluster proportional random sampling. Tests and observation were utilized to collect the data. The Pearson product moment correlations and the Wherry-Doollitle multiple correlations suggest that the test items of serving and down passing were reliable and valid to measure the students’ ability in playing volley ball.